2022
DOI: 10.1111/sji.13174
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut microbiota in the immunopathology of atherosclerosis: Focus on immune cells

Abstract: Gut microbiota (GM) plays important roles in multiple organ function, homeostasis and several diseases. More recently, increasing evidences have suggested that the compositional and functional alterations of GM play a crucial role in the accumulation of foam cells and the formation of atherosclerotic plaque in atherosclerosis. In particular, the effects of bacterial components and metabolites on innate and adaptive immune cells have been explored as the underlying mechanisms. Understanding the effects of GM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 133 publications
(276 reference statements)
0
3
0
Order By: Relevance
“…Trimethylamine-N-oxide (TMAO), a metabolite produced from dietary precursors in the liver by trimethylamine (TMA) oxidization, has been explored in previous studies [13,14]. Extensive clinical and animal studies have concluded that TMAO promotes atherosclerosis through multiple mechanisms, such as cholesterol accumulation, inflammatory cell recruitment, and endothelial dysfunction [3,[13][14][15]. Elevated TMAO levels predict greater incidence of adverse events in patients with CAD and PAD [16].…”
Section: Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Trimethylamine-N-oxide (TMAO), a metabolite produced from dietary precursors in the liver by trimethylamine (TMA) oxidization, has been explored in previous studies [13,14]. Extensive clinical and animal studies have concluded that TMAO promotes atherosclerosis through multiple mechanisms, such as cholesterol accumulation, inflammatory cell recruitment, and endothelial dysfunction [3,[13][14][15]. Elevated TMAO levels predict greater incidence of adverse events in patients with CAD and PAD [16].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Accumulating evidence indicates crosstalk between the gut microbiota and vascular dysfunction, thus extending the scope of therapy for atherosclerosis, aneurysm, and VC (Table 1) [73,74]. Dietary modulation is a viable and acceptable means of decreasing chronic vascular inflammation [3,15]. Specifically, the abovementioned natural products show powerful anti-inflammatory effects with minimal adverse effects [25].…”
Section: Potential Therapy Targeting the Gut Microbiota And Metabolitesmentioning
confidence: 99%
“…Of these, 18 are review articles covering a wide range of disease and non-disease states, e.g., cancer [23][24][25], cardiovascular disease (CVD) [26], autism [19], type 2 diabetes [27]. Notably, five review papers focussed on the microbiome [25,[28][29][30][31]. While it is not possible to synthesize the findings of all 30 papers, we collate them in Table 3, and offer remarks on a select few that highlight a true personalized medicine or precision medicine approach to nutraceutical use.…”
Section: Scopementioning
confidence: 99%